2021
DOI: 10.3803/enm.2021.1069
|View full text |Cite
|
Sign up to set email alerts
|

Cushing Syndrome Associated Myopathy: It Is Time for a Change

Abstract: Cushing syndrome is the result of excessive levels of glucocorticoids. Endogenous Cushing syndrome is rare with an incidence of two to three cases per million per year. Clinically, the presentation consists of a characteristic phenotype including skin symptoms and metabolic manifestations. A frequent co-morbidity with high impact on quality of life is Cushing syndrome associated myopathy. It characteristically affects the proximal myopathy, impairing stair climbing and straightening up. The pathophysiology is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 71 publications
1
18
0
Order By: Relevance
“…The pathology is multifactorial, including protein degradation through the forkhead box O3 (FOXO3) pathway as well as accumulation of intramuscular fat and inactivity-associated muscle atrophy. 135 Furthermore, hypercortisolism remission can induce exacerbation of pre-existing autoimmune disorders.…”
Section: Other Complicationsmentioning
confidence: 99%
“…The pathology is multifactorial, including protein degradation through the forkhead box O3 (FOXO3) pathway as well as accumulation of intramuscular fat and inactivity-associated muscle atrophy. 135 Furthermore, hypercortisolism remission can induce exacerbation of pre-existing autoimmune disorders.…”
Section: Other Complicationsmentioning
confidence: 99%
“…Furthermore, the changes in IGF‐1 in patients from the time of diagnosis to 6 months after surgery were good predictors of an improvement in grip strength, with significant changes being positive predictors of recovery 34 . Based on these pathophysiological considerations, growth hormone therapy was proposed as a treatment option for myopathy in CS, particularly after transsphenoidal surgery and with an insufficiency of the somatotropic axis, but randomised trials are lacking 35 . Notably, epidemiological data showed an association of growth hormone replacement in patients with CS in remission and improved long‐term survival 36 …”
Section: Frequency and Management Of Selected Comorbiditiesmentioning
confidence: 99%
“…Importantly, the 11BHSD1 inhibition was found to counteract the GC-induced decrease in protein synthesis and increase in protein degradation, suggesting a potential role for 11BHSD1 inhibitors to ameliorate muscle-wasting effects associated with GC excess. In line with these data, recently in a small study, the 11BHSD1 inhibitor S-707106 demonstrated an effective insulin sensitizer, anti-sarcopenic and anti-obesity effect in both Cushing’s syndrome and mHC patients [ 108 , 109 , 110 , 111 , 112 , 113 ].…”
Section: Pathophysiology Of the Systemic Consequences Of Mild Hypercortisolismmentioning
confidence: 61%
“…The former mechanisms include the decrease in amino-acid uptake by muscle; the inhibition of insulin-like growth factor 1 secretion, which is crucial for the rapamycin pathway and the inhibition of myogenin, which is essential for myogenesis and the stimulation of myostatin [ 98 , 108 , 109 ]. The GC excess-mediated catabolic action on muscle is mainly related to enhanced proteolysis, due to alterations of the ubiquitin–proteosome system and to impairment of sarcolemma excitability [ 110 ], via effects on the muscle-ring finger protein-1 (MuRF1) and atrogin-1, both target cellular proteins to the proteosome for hydrolysis [ 108 ]. Interestingly, the decrease in insulin-like growth factor 1 levels due to GC excess may also have catabolic effects, since it was suggested to be associated with a decrease in mTOR activation and increased mRNA expression of MuRF1 and myostatin [ 108 , 111 ].…”
Section: Pathophysiology Of the Systemic Consequences Of Mild Hypercortisolismmentioning
confidence: 99%
See 1 more Smart Citation